Molecular mechanisms of renal and extrarenal manifestations caused by inactivation of the electrogenic Na+-HCO3− cotransporter NBCe1 - Seki, George; Horita, Shoko; Suzuki, Masashi; Yamazaki, Osamu; Usui, Tomohiko; Nakamura, Motonobu; Yamada, Hideomi (Frontiers in Physiology, 2013)
The electrogenic Na+-HCO3- cotransporter NBCe1 plays an essential role in bicarbonate absorption from renal proximal tubules, but also mediates the other biological processes in extrarenal tissues such as bicarbonate secretion from pancreatic ducts, maintenance of tissue homeostasis in eye, enamel maturation in teeth, or local pH regulation in synapses. Homozygous mutation in NBCe1 cause proximal renal tubular acidosis (pRTA) associated with extrarenal manifestations such as short stature, ocular abnormalities, enamel abnormalities, and migraine. Functional analyses of NBCe1 mutants using different expression systems suggest that at least a 50% reduction of the transport activity may be required to induce severe pRTA. In addition to functional impairments, some NBCe1 mutants show trafficking defects. Some of the pRTA-related NBCe1 mutants showing the cytoplasmic retention have been shown to exert a dominant negative effect through hetero-oligomer complexes with wild-type NBCe1 that may explain the occurrence of extrarenal manifestations in the heterozygous carries of NBCe1 mutations. Both NBCe1 knockout and W516X knockin mice showed very severe pRTA and reproduced most of the clinical manifestations observed in human pRTA patients. Functional analysis on isolated renal proximal tubules from W516X knockin mice directly confirmed the indispensable role of NBCe1 in bicarbonate absorption from this nephron segment. In this review, we will focus on the molecular mechanisms underling the renal and extrarenal manifestations caused by NBCe1 inactivation.